2008
DOI: 10.4321/s1130-01082008000300002
|View full text |Cite
|
Sign up to set email alerts
|

Factores pronósticos de complicaciones postoperatorias en el trasplante hepático

Abstract: INTRODUCCIÓNEl trasplante hepático ortotópico (THO) es el tratamiento de elección para enfermedades hepáticas agudas o crónicas en estadio final. Sin embargo, el seguimiento de Factores pronósticos de complicaciones postoperatorias en el trasplante hepáticoA. Rodríguez-Ariza, A. Monrobel, E. Martínez-Galisteo 1 , C. Alicia Padilla 1 , J. A. Bárcena 1 , E. Fraga, G. Costán, P. Barrera, A. Poyato, J. L. Montero, P. López-Cillero 2 , J. Muntané y M. de la Mata RESUMENObjetivo: la evolución postoperatoria de los … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
1
0
1
Order By: Relevance
“…Nair et al . [8] showed that pre-operative serum level of creatinine (>1.5 mg/dl) was an important indicator for assessing post-operative ICU stay as well as short-term survival rate [20], [21], [22]. These results imply that it is better to perform liver transplantation before renal function becomes impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Nair et al . [8] showed that pre-operative serum level of creatinine (>1.5 mg/dl) was an important indicator for assessing post-operative ICU stay as well as short-term survival rate [20], [21], [22]. These results imply that it is better to perform liver transplantation before renal function becomes impaired.…”
Section: Discussionmentioning
confidence: 99%
“…No parece que se haya observado influencia de la inmunosupresión, cuando se realiza con ciclosporina o tacrolimus, en el desarrollo de complicaciones neurológicas en las diferentes publicaciones realizadas, al igual que ha evidenciado la de Rodríguez-Ariza y cols. (2). En el año 1994, Mueller y cols.…”
Section: Complicaciones Precoces Tras El Trasplante Hepático ¿Podemounclassified